Role of Siglecs and Related Glycan-Binding Proteins in Immune Responses and Immunoregulation - Bochner, Bruce S. (J Allergy Clin Immunol, 2015)
Eukaryotic cells and extracellular material are heavily decorated by various glycans, yet the understanding of the structure and function of these moieties lags behind our understanding of nucleic acids, lipids and proteins. Recent years have seen a tremendous acceleration of understanding in the field of glycobiology, revealing many intricacies and functional contributions that were previously poorly understood or even unrecognized. This review highlights several topics relevant to glycoimmunology, where mammalian and pathogen-derived glycans displayed on glycoproteins and other scaffolds are recognized by specific glycan-binding proteins (GBPs), leading to a variety of pro- and anti-inflammatory cellular responses. The focus for this review is mainly on two families of GBPs, siglecs and selectins, that are involved in multiple steps of the immune response, including distinguishing pathogens from self, cell trafficking to sites of inflammation, fine-tuning of immune responses leading to activation or tolerance, and regulation of cell survival. Importantly for the clinician, accelerated rates of discovery in the field of glycoimmunology are being translated into innovative medicinal approaches that harness the interaction of glycans and GBPs to the benefit of the host, and may soon lead to novel diagnostics and therapeutics.